Thermal Structural Transitions and Carbon Dioxide Adsorption Properties of Zeolitic Imidazolate Framework-7 (ZIF-7) - Cai, Wanxi; Lee, Taehee; Lee, Maro; Cho, Woosuk; Han, Doug-Young; Choi, Nakwon; Yip, Alex C. K.; Choi, Jungkyu (AMER CHEMICAL SOC, 2014)
As a subset of the metal-organic frameworks, zeolitic imidazolate frameworks (ZIFs) have potential use in practical separations as a result of flexible yet reliable control over their pore sizes along with their chemical and thermal stabilities. Among many ZIF materials, we explored the effect of thermal treatments on the ZIF-7 structure, known for its promising characteristics toward H-2 separations; the pore sizes of ZIF-7 (0.29 nm) are desirable for molecular sieving, favoring H-2 (0.289 nm) over CO2 (0.33 nm). Although thermogravimetric analysis indicated that ZIF-7 is thermally stabile up to similar to 400 degrees C, the structural transition of ZIF-7 to an intermediate phase (as indicated by X-ray analysis) was observed under air as guest molecules were removed. The transition was further continued at higher temperatures, eventually leading toward the zinc oxide phase. Three types of ZIF-7 with differing shapes and sizes (similar to 100 nm spherical, similar to 400 nm rhombic-dodecahedral, and similar to 1300 nm rod-shaped) were employed to elucidate (1) thermal structural transitions while considering kinetically relevant processes and (2) discrepancies in the N-2 physisorption and CO2 adsorption isotherms. The largest rod-shaped ZIF-7 particles showed a delayed thermal structural transition toward the stable zinc oxide phase. The CO2 adsorption behaviors of the three ZIF-7s, despite their identical crystal structures, suggested minute differences in the pore structures; in particular, the smaller spherical ZIF-7 particles provided reversible CO2 adsorption isotherms at similar to 30-75 degrees C, a typical temperature range of flue gases from coal-fired power plants, in contrast to the larger rhombic-dodecahedral and rod-shaped ZIF-7 particles, which exhibited hysteretic CO2 adsorption/desorption behavior.
Keywords: METAL-ORGANIC FRAMEWORK; MOLECULAR-SIEVE MEMBRANE; MIXED-MATRIX MEMBRANES; SURFACE PERMEABILITIES; HYDROGEN SELECTIVITY; ATOMISTIC SIMULATION; SODALITE TOPOLOGY; SEPARATION; CAPTURE; GATE